Modified Ashworth Scale (MAS) integrated adaptive impedance control framework for upper extremity training platform - Sidek, Shahrul Na'im; Mat Rosly, Muhammad Hadi; Md. Yusof, Hazlina; Puzi, Asmarani; Daud, Narimah; Mat Rosly, Maziah (IEEE, 2017)
Robotic training platform are sought out for their promising therapeutic assistance. However, distinctive advancement has yet to resolve the monotonous and lopsided aspect of current system. Thus, this paper proposes the integration of Modified Ashworth Scale (MAS)-based assessment with dynamic impedance control model, presenting an artificial compliance within the robotic assisted training platform control framework. This enhancement is hypothesised to allow better accommodation of subject’s user input under specified training regimen. Feasibility study was verified via simulation of acceleration-based impedance model under MAS 0 and 1+ contraints for linear forward motion training regimen involving elbow extension.